2015
DOI: 10.1111/jth.12922
|View full text |Cite
|
Sign up to set email alerts
|

The role of circulating platelet transcripts

Abstract: Summary Our understanding of platelets, anucleate cells with a traditional role in hemostasis and inflammation, has developed greatly over the last decade. Platelets' role in the systemic response of the body to vascular injury, inflammation, and infection has expanded as has our understanding of their importance to the body's regulation of these processes. One recently explored mechanism by which platelets regulate the body's inflammatory and immune response is through its endogenous RNA. Platelets' messenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…While platelets are anucleate cells, they have been demonstrated to possess a complex transcriptome derived from both their cell of origin, but also from other tissues including tumors, through processes including microvesicle-mediated exchange. 23 Platelets possess a range of RNA molecules, including messenger RNA (mRNA) transcripts representative of approximately 5,000 genes. 24 Pre-mRNA molecules can be processed by platelet resident spliceosome machinery 25 and there are also complex and dynamic populations of regulatory microRNAs, long noncoding RNAs, and circular RNAs.…”
Section: Liquid Biopsiesmentioning
confidence: 99%
“…While platelets are anucleate cells, they have been demonstrated to possess a complex transcriptome derived from both their cell of origin, but also from other tissues including tumors, through processes including microvesicle-mediated exchange. 23 Platelets possess a range of RNA molecules, including messenger RNA (mRNA) transcripts representative of approximately 5,000 genes. 24 Pre-mRNA molecules can be processed by platelet resident spliceosome machinery 25 and there are also complex and dynamic populations of regulatory microRNAs, long noncoding RNAs, and circular RNAs.…”
Section: Liquid Biopsiesmentioning
confidence: 99%
“…A critical transcription factor for megakaryocyte development and thrombopoiesis is RUNX1, which has been shown to repress the erythroid gene expression program, thus facilitating megakaryocyte differentiation 22. Furthermore, RUNX1 regulates cytoskeletal genes such as MYH9 and MYH10 and plays a role in megakaryocyte ploidy and proplatelet formation 23, 24, 25. ETV6, a member of the ETS transcription factor family, is required for late megakaryopoiesis and hematopoietic stem cell survival 26.…”
Section: Genetic Regulation Of Normal Megakaryopoiesismentioning
confidence: 99%
“…While they have been shown to play a crucial role, numerous recent studies have demonstrated further complexity in the system. miRNAs and ribonucleases (ie, Dicer1) which modulate gene expression appear to play an important role in the biology of hematopoiesis and hemostasis 23, 30. Lu et al.…”
Section: Genetic Regulation Of Normal Megakaryopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…The platelets’ defined biological roles have expanded exponentially over the last decade to include immunity, inflammation and mediation of oncogenesis. 1 Platelets, although anucleate, contain a wealth of transcriptomic information. When viewed from the perspective of a large population analysis, platelets demonstrate wide diversity, important patterns, including association with obesity and diabetes, and distinct expression profiles as compared to white cells.…”
mentioning
confidence: 99%